2019
DOI: 10.3892/ijo.2019.4733
|View full text |Cite
|
Sign up to set email alerts
|

ZNF692 promotes colon adenocarcinoma cell growth and metastasis by activating the PI3K/AKT pathway

Abstract: Despite considerable recent advancements in colorectal cancer (CRC) therapy, the prognosis of patients with advanced disease remains poor. Further understanding of the molecular mechanisms and treatment strategies of this disease is required. Zinc finger protein 692 (ZNF692), also known as AREBP and Zfp692, was first reported to have an important role in gluconeogenesis. A recent study demonstrated that ZNF692 is overexpressed in lung adenocarcinoma (LUAD) tissues and that ZNF692 knockdown inhibited LUAD cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
26
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 47 publications
4
26
1
Order By: Relevance
“…It has been confirmed that the PI3K/Akt pathway activation plays an important role in promoting placental development, fetal growth, and GDM in humans and rodents [ 34 , 35 ]. Moreover, the PI3K/Akt signaling pathway is important for cell proliferation, migration, invasion, and gluconeogenesis [ 36 ]. Past studies have demonstrated that the inhibition of the PI3K/Akt signaling pathway can reduce oxidative stress, affect the function of trophoblast cells, and reduce the blood glucose level in a GDM rat model [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been confirmed that the PI3K/Akt pathway activation plays an important role in promoting placental development, fetal growth, and GDM in humans and rodents [ 34 , 35 ]. Moreover, the PI3K/Akt signaling pathway is important for cell proliferation, migration, invasion, and gluconeogenesis [ 36 ]. Past studies have demonstrated that the inhibition of the PI3K/Akt signaling pathway can reduce oxidative stress, affect the function of trophoblast cells, and reduce the blood glucose level in a GDM rat model [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pi3K/akt/mTor is a crucial signaling pathway involved in the carcinogenicity and tumorigenesis of different cancer types, and is closely related to cell biological functions, such as energy metabolism, proliferation, apoptosis and cell invasion (16)(17)(18)(19). Previous studies have revealed that certain mrnas are co-expressed with cYP2e1 and participate in the Pi3K/akt/mTor signaling pathway (20,21).…”
Section: Cyp2e1 Regulates Key Pi3k/akt/mtor Signaling Proteinsmentioning
confidence: 99%
“…CBX3 has been confirmed to promote cell cycle transition by inducing CDK1 and PCNA 79 . The elevated POU5F1 in LIHC may influence the expression of CBX3 and then activate the NF‐Kβ and PI3K/Akt pathways through BARD1 and ZNF692 80,81 . The promotion effect of CCND2 on cell proliferation is regulated by NFYC and may also be affected by POU5F1 82 .…”
Section: Discussionmentioning
confidence: 98%
“…79 The elevated POU5F1 in LIHC may influence the expression of CBX3 and then activate the NF-Kβ and PI3K/Akt pathways through BARD1 and ZNF692. 80,81 The promotion effect of CCND2 on cell proliferation is regulated by NFYC and may also be affected by POU5F1. 82 The interaction between NFYC and KAT2A indicates that POU5F1 participates in tumor development through KAT2A-mediated histone H3 succinylation.…”
Section: Discussionmentioning
confidence: 99%